COMPETITIVENESS OF METAL PRODUCTION OF RUP ‘BMZ» ON THE INTERNATIONAL COMMODITY MARKETS - M. V. Kuzmich (Литьë и металлургия)
It is shown that the received integral indices of competitiveness testify to the fact that production is on the high level of competitiveness on world markets of sales and is approximately on one position with the best goods-analogues.